The Review of Modes of Operation and Randomization in Smartphone Passive Monitoring using WI-FI Probe Context - Maikaensarn, Vikrom (INTERNATIONAL SCIENTIFIC JOURNAL OF ENGINEERING AND TECHNOLOGY (ISJET), 2021)
WI-FI probe monitoring is a passive monitoring technique that collects information from the smartphone’s probe request information, using a sensor or sniffer, representing the monitored area’s users. Nonetheless, as technologies developed, more changes are applied to the smartphone, promoting the user’s privacy protection and extending the device’s functionality. At the same time, this caused a shift in the smartphone device’s probing behavior, which affects the effectiveness of WI-FI probe monitoring. In this study, by reviewing different factors that may affect smartphone WI-FI probe monitoring effectiveness, it was found that developers have adopted the MAC address randomization process in response to the user’s privacy protection. Although randomization caused noises in the data and altered the study’s outcome while the smartphone device is not connected to the internet, it is possible to monitor the users connected to the internet with the proper SSID and network structure setup.